16TH- AND 17TH-CENTURY ITALIAN CHIAROSCURO WOODCUTS: INSTRUMENTAL ANALYSIS, DEGRADATION, AND CONSERVATION. Issue 4 (November 2015) - Morenus, Linda Stiber; Eng, Charlotte W.; Takahatake, Naoko; Rambaldi, Diana C.
Abstract : Italian chiaroscuro woodcuts are among the most technically innovative of Renaissance prints for being printed in color. A woodcut is made from a wooden plank that is carved in relief, inked, and impressed on paper. Chiaroscuro woodcut prints – named from the Italian term for contrasting light and dark tones – involve printing an image from two or more woodblocks, with each block printed in a different color, to create transitional passages of shading. With two to five superimposed layers of colored, oil-based inks printed onto a paper support, the chiaroscuro woodcut is an object of complex stratigraphy. Several centuries of aging and deterioration of both the inks and paper can cause visual changes that affect a print's legibility, thereby distorting the historical and aesthetic interpretation of the work. A correct assessment of the physical characteristics of the printing process and the colored inks deployed, as well as the condition of the woodcut, is therefore fundamental not only to the art-historical evaluation of prints, but equally to the application of appropriate preservation and conservation measures. A technical survey of over 2000 Italian chiaroscuro woodcuts of the 16th and 17th centuries examined in international collections revealed trends in deterioration of colored inks such as discoloration, fading, blanching, and micro-fissures. Seventy-two prints from the Library of Congress, Los Angeles County Museum of Art, and Grunwald Center for the Graphic Arts were examined further using instrumental analysis. The results of this joint study demonstrate the use of unstable colorants such as lead white, verdigris, vermilion, orpiment, and organic pigments. Based on the documented behavior of unstable colorants in oil paint, it is possible to infer how the visual appearance of prints containing such colorants is likely to have changed. The combined evidence is here analyzed in order to establish recommendations for conservation treatment, storage, and parameters for display and equally to inform art-historical interpretation.